English Language Acquisition (ELA) Among Pelindo Employees: Analysis of English Acquisition for Business Communication in The Workplace - Windari, Devi; Ashari, Erwin; Ainun, Nur (Universitas Negeri Medan, 2024)
This study examines Business English acquisition patterns among employees at Pelindo, Indonesia's largest port operator, focusing on workplace communication challenges in an increasingly globalized maritime industry. Through qualitative case study methodology, the research surveyed 50 employees across various divisions using a mixed-method questionnaire combining Likert-scale assessments and open-ended responses. Results indicate high employee motivation for Business English acquisition (mean 3.50) driven by professional demands, yet reveal significant challenges in legal terminology comprehension (mean 2.95) and complex business document creation (mean 3.20). The study found that technology integration in learning processes (mean 3.80) and case-study approaches (mean 3.50) significantly enhance Business English acquisition effectiveness. These findings contribute to understanding specialized language acquisition in state-owned enterprises, particularly in maritime logistics contexts, and suggest the need for integrated learning approaches combining formal instruction with authentic business communication practice. The research implications are particularly relevant for developing targeted language training programs in international port operations contexts.